Evaluation on the process parameters influencing the surface texture using open-source 3D printing - Sukindar, Nor Aiman; Mohd Ariffin, Mohd Khairol Anuar; Baharudin, B.T. Hang Tuah; Jaafar, Che Nor Aiza; Ismail, Mohd Idris Shah (Malaysian Tribology Society, 2016)
Fused deposition modeling (FDM) or three-dimensional (3D) printing is becoming ubiquitous today because it allows the fabrication of 3D products directly from computer-aided design software. The quality of 3D parts is influenced by several parameters that need to be carefully tuned to obtain a high-quality final product. The surface finish of the finished parts is one of the major factors to consider because it affects both the dimensional accuracy and the functionality of the piece. Thus, the present study focuses on improving the surface finish of parts produced by FDM by manipulating different parameters such as layer height, raster angle, extruder temperature, printing speed, and percent infill. Polylactic acid was used in this study, which is a material present in filament form, and was extruded using a newly developed 3D printer; the design-of-experiment method was used to design the experiment. The results indicate that raster angle and extruder temperature are the most influential process parameters. The results show that raster angle and extruder temperature exert the strongest influence on the surface quality of the final product.